DERMATOGLIFI UJUNG JARI DAN TELAPAK TANGAN PENDERITA TUNAGRAHITA DI SEKOLAH LUAR BIASA SAWAHLUNTO - -, Oktarina - (STKIP PGRI Sumbar, 2014)
Dermatogliphy formed by many genes. Fingerprint patterns can be used to identify the perpetrators of thecrime and prosecuted, and also can be used to diagnose a genetic disease or genetic disorders. One of theinteresting genetic disease to be observed in relation to dermatogliphy is mentally retarded. This study used apurposive sampling method for the mentally retarded group and random sampling for the normal group. Thepercentage of the fingerprint patterns were analyzed by using chi-square X2. From the data obtained it appearsthat the percentage of fingerprint patterns between normal and mentally retarded group, where the percentageof mentally retarded arch = 9 %. While the normal group arch = 0 %. Statistically testing the chi-square testshowed that the fingerprint pattern and the mentally retarded group normal group there is significant. Thenumber of mentally retarded children tendrils fingertips lower than the normal group by t test there issignificant at p = 0,05. Percentage frequency palm tendril pattern where the percentage of mentally retardedgroup I2 = 2,5 % , while the normal group I2= 0 %. Based on the statistical test t-student test large atd anglementally retarded and normal children showed no significant differences at p = 0,05 .